Julián Seller, un escultor aragonés en la Lleida del siglo XVIII : Julián Seller, an Aragonese sculptor in Lleida in the 18th century - Puig Sanchís, Isidro (Artigrama, 2023)
ResumenEl presente trabajo aporta nuevas referencias documentales de la labor profesional realizada por el escultor aragonés Julián Seller en ‘les Terres de Lleida’. La única referencia que hasta este momento situaba a Seller como residente en Lleida era la capitulación del retablo mayor de la localidad de Pozán de Vero, de 1758. Queremos ahora dar a conocer sus trabajos escultóricos realizados en la misma capital del Segre, y en concreto en su nueva catedral, así como en localidades cercanas, como Massalcoreig y Borges Blanques, además de constatar que seguramente estuvo trabajando en Albalate de Cinca y en Fraga.AbstractThe present work provides new documentary references of the professional work carried out by the Aragonese sculptor Julián Seller in ‘les Terres de Lleida’. The only reference that until now placed Seller as a Lleida resident was the capitulation of the main altarpiece of the town of Pozán de Vero, from 1758. We now want to publicize his sculptural works carried out in the Segre capital itself, and specifically in his new Cathedral, as well as in nearby towns, such as Massalcoreig and Borges Blanques, in addition to verifying that he was surely working in Albalate de Cinca and Fraga.KeywordsAragón, Lleida, Sculpture, Century XVIII, Julián Seller, New Cathedral, Massalcoreig.